Tight Xenon Confinement in a Crystalline Sandwich‐like Hydrogen‐Bonded Dimeric Capsule of a Cyclic Peptide. (5th September 2019) - Pizzi, Andrea; Ozores, Haxel Lionel; Calvelo, Martín; García‐Fandiño, Rebeca; Amorín, Manuel; Demitri, Nicola; Terraneo, Giancarlo; Bracco, Silvia; Comotti, Angiolina; Sozzani, Piero; Bezuidenhout, Charl X.; Metrangolo, Pierangelo; et al.
Abstract: A cyclic hexapeptide with three pyridyl moieties connected to its backbone forms a hydrogen‐bonded dimer, which tightly encapsulates a single xenon atom, like a pearl in its shell. The dimer imprints its shape and symmetry to the captured xenon atom, as demonstrated by 129 Xe NMR spectroscopy, single‐crystal X‐ray diffraction, and computational studies. The dimers self‐assemble hierarchically into tubular structures to form a porous supramolecular architecture, whose cavities are filled by small molecules and gases. Abstract : Eng eingeschlossen : Ein cyclisches Hexapeptid mit drei Pyridylgruppen an der Hauptkette bildet ein wasserstoffbrückengebundenes Dimer, das ein einzelnes Xenon‐Atom eng einkapselt. Die Dimere ordnen sich hierarchisch zu röhrenartigen Strukturen in einer porösen supramolekularen Architektur an, deren Hohlräume durch kleine Moleküle und Gase ausgefüllt werden können.